2012
DOI: 10.1254/jphs.12075fp
|View full text |Cite
|
Sign up to set email alerts
|

N-type Calcium Channel Inhibition With Cilnidipine Elicits Glomerular Podocyte Protection Independent of Sympathetic Nerve Inhibition

Abstract: We recently demonstrated that cilnidipine, an L/N-type calcium channel blocker, elicits protective effects against glomerular podocyte injury, in particular, in obese hypertensive rats that express the N-type calcium channel (N-CC). Since the N-CC is known to be expressed in sympathetic nerve endings, we evaluated the reno-protective effects of cilnidipine in innervated and denervated spontaneously hypertensive rats (SHR). Male SHR were uninephrectomized and fed 4% high-salt diet (HS-UNX-SHR). Animals were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Several studies have suggested that the increase in renal Ang II level contributes to the development of renal disease (23, 3941). However, there was no difference in proteinuria at week 4 of Ang I infusion between temocapril- and olmesartan-treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that the increase in renal Ang II level contributes to the development of renal disease (23, 3941). However, there was no difference in proteinuria at week 4 of Ang I infusion between temocapril- and olmesartan-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotide primer sequences of GAPDH and AGT and PCR conditions were as described previously (23, 24). The primer sequences of ACE2 were as follows: ACE2 forward, 5′-CCCAGAGAACAGTGGACCAAAA-3′ and reverse, 5′-GCTCCACCACACCAACGAT-3′.…”
Section: Methodsmentioning
confidence: 99%
“…L/Ntype CCBs has been shown to provide renal protection by decreasing the activity of the sympathetic nervous system and the RAAS, resulting in vasodilation of both arterioles, inhibition of podocyte injury and decrease in proteinuria. [44][45][46][47][48] With respect to L/T-type CCBs, T-type channels have an important role in the kidney, mediating efferent arteriole tone, and combined T-and L-type CCBs might have a therapeutic advantage over selective L-type CCBs by providing renoprotection via a lower glomerular pressure and filtration fraction. 49 Hypertension and proteinuria are well-recognized risk factors for predicting progression of CKD 10 and cardiovascular morbidity and mortality.…”
Section: Renal Effects Of N-and T-type Ccbmentioning
confidence: 99%
“…However, in addition to these actions, we showed possible functional roles of the N-type calcium channel in podocytes. Previous reports showed that glomerular podocytes express the N-type calcium channel 13 27 . Fan et al .…”
Section: Discussionmentioning
confidence: 98%
“…Because N-type calcium channels exist at synaptic nerve endings 26 in both the afferent and efferent arterioles, and the blockade of the N-type calcium channel inhibits norepinephrine release 26 , such sympatholytic effect of the N-type calcium channel ablation may have worked to ameliorate glomerular injury in our study. Cilnidipine showed similar antihypertensive effects and suppression of proteinuria both in innervated and denervated spontaneous hypertensive rat (SHR) 27 , thus suggesting that renal sympathetic nerves may have a limited contribution to its renoprotective effects. In our study, albuminuria as well as glomerular histological changes were significantly alleviated in db/db Ca v 2.2 +/− mice and cilnidipine-treated diabetic mice without reduction of urinary catecholamine levels, further providing a possibility for mechanisms independent of the sympathetic nerve activity.…”
Section: Discussionmentioning
confidence: 99%